1999
DOI: 10.1002/(sici)1098-2744(199906)25:2<86::aid-mc2>3.0.co;2-4
|View full text |Cite
|
Sign up to set email alerts
|

Effects of fixation on RNA extraction and amplification from laser capture microdissected tissue

Abstract: One of the key end points for understanding the molecular basis of carcinogenesis is the quantitation of gene expression in specific cell populations. Microdissection techniques allow extraction of morphologically distinct cells for molecular analysis. A recent advance in microdissection uses the PixCell laser capture microdissection (LCM) system, which allows for precise removal of pure cell populations from morphologically preserved tissue sections. The objective of this study was to determine the optimal fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
107
1
2

Year Published

2001
2001
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 299 publications
(117 citation statements)
references
References 13 publications
7
107
1
2
Order By: Relevance
“…In addition, there was evidence for RNA degradation (no peaks detected). These observations are consistent with published reports that used denaturing agarose gel electrophoresis to show that paraformaldehyde treatment decreased both the recovery and quality of RNA extracted from brain (14)(15)(16)(17).…”
Section: Integrity Of Rnasupporting
confidence: 92%
See 2 more Smart Citations
“…In addition, there was evidence for RNA degradation (no peaks detected). These observations are consistent with published reports that used denaturing agarose gel electrophoresis to show that paraformaldehyde treatment decreased both the recovery and quality of RNA extracted from brain (14)(15)(16)(17).…”
Section: Integrity Of Rnasupporting
confidence: 92%
“…This would give the incorrect impression of diminished recovery and/or degradation, which was the explanation provided in the literature (14)(15)(16). Consistent with the notion that paraformaldehyde crosslinks but does not degrade RNA, this fixation method is commonly employed for in situ hybridization and does not seem to appreciably degrade RNA in that setting.…”
Section: Microarray Analysis Of Brain Rnamentioning
confidence: 73%
See 1 more Smart Citation
“…Results from the control KG-1a cells from the cord blood experiment confirmed this finding, since the cells that went through the sort process matched the unsorted cells, with an R 2 -value of 0.99. We concluded that for meaningful gene expression microarray profiling a minor cell subset of a cell mixture, purification of these cells is not only necessary, but also very much achievable, recovering the "pure profile" without any significant distortion, despite the concerns expressed previously in the literature (18,33,39). In our hands, following the procedures described in this work, the effects of sample handling on the GEP were minimal and not significant.…”
Section: Discussionmentioning
confidence: 62%
“…The next question was, how much distortion would the purification process itself (including cell fixation, labeling, and sorting) introduce into the studied GEP? We tested methanolfixation, since alcohols are known to preserve nucleic acids better than cross-linking agents (39). Figure 3A shows a GEP scatterplot of live, unlabeled CEM cells and antibody-labeled, methanol-postfixed CEM cells.…”
Section: Effects Of Sample Handlingmentioning
confidence: 99%